Adult atrial septal defect device closure with floppy rims (Indian Journal of Case Reports, 2021)
Floppy rims of atrial septal defect (ASD) preclude device closure as those rims do not hold the device with a high risk of device dislodgement and embolization. In spite of the floppiness if the margins have an adequate length (>5 mm), sometimes it may also hold the oversized device obviating the need for surgical closure. We report a successful closure of an adult 30 mm ostium secundum ASD with floppy posterosuperior and inferior vena cava rim with Amplatzer 34 mm device. “Oversize the device in floppy rims” is the only clue to get success in those cases. Sometimes, a fair trial against nature’s negativity can also result in a successful outcome.